High output power, fibre‐coupled distributed feedback lasers operating near 2.05 μm wavelength range. Issue 24 (1st November 2013) - Bagheri, M.; Frez, C.; Kelly, B.; Gupta, J.A.; Forouhar, S.
Abstract : Single‐mode operation of fibre‐pigtailed distributed feedback semiconductor lasers in the 2.05 μm range has been demonstrated. The lasers are packaged inside standard butterfly modules with output powers in excess of 10 mW at the end of polarisation maintaining optical fibre. The fibre‐pigtailed lasers show excellent sidemode suppression ratios (> 50 dB) and have a mode‐hop free tunability larger than 1 nm. The output of the optical fibre has linear polarisation with better than 20 dB extinction over the operating current and temperatures.